Electrospun composite nanofiber membrane of poly(l-lactide) and surface grafted chitin whiskers: Fabrication, mechanical properties and cytocompatibility. (20th August 2016) - Liu, Hua; Liu, Wenjun; Luo, Binghong; Wen, Wei; Liu, Mingxian; Wang, Xiaoying; Zhou, Changren
Highlights: The CHWs were prepared and further surface modified with PLLA to obtain g -CHWs. The g -CHWs can disperse more uniformly in PLLA matrix than CHWs. The interfacial adhesion between g -CHWs and PLLA matrix was obviously improved. Tensile property of g -CHWs/PLLA fiber membrane are superior to PLLA and CHWs/PLLA. The g -CHWs/PLLA fiber membrane is more suitable for cell adhesion and growth. Abstract: To improve both the mechanical properties and cytocompatibility of poly(l -lactide) (PLLA), rod-like chitin whiskers (CHWs) were prepared, and subsequently surface modified withl -lactide to obtain grafted CHWs ( g -CHWs). Then, CHWs and g -CHWs were further introduced into PLLA matrix to fabricate CHWs/PLLA and g -CHWs/PLLA nanofiber membranes by electrospinning technique. Morphologies and properties of the CHWs and g -CHWs were characterized. The surface-grafted PLLA chains played an important role in improving interfacial interaction between the whiskers and PLLA matrix. The g -CHWs dispersed more uniformly in matrix than CHWs, and the as-prepared g -CHWs/PLLA nanofiber membrane showed relative smooth and uniform fiber. As a result, the tensile strength and modulus of the g -CHWs/PLLA nanofiber membrane were obviously superior to those of the pure PLLA and CHWs/PLLA nanofiber membranes. Cells culture results indicated that g -CHWs/PLLA nanofiber membrane is more effectively in promoting MC3T3-E1 cells adhesion, spreading and proliferation than pure PLLA and CHWs/PLLA nanofiber membrane.